2000
DOI: 10.1071/wr99030
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the numbers of red kangaroos and emus on either side of the South Australian dingo fence: evidence for predator regulation?

Abstract: Most of Australia’s sheep rangelands are enclosed by a dingo-proof fence. Within these rangelands, where dingoes (Canis lupus dingo) are rare, red kangaroos (Macropus rufus) are considered to be food limited because their numbers respond to fluctuations in pasture biomass that are driven by highly variable rainfall. Outside this region, where dingoes are common, kangaroo densities are generally substantially lower, suggesting that dingoes are an important limiting factor. However, it is unclear whether dingoes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
91
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 27 publications
11
91
0
Order By: Relevance
“…The wide array of adaptive responses to periods of low rainfall displayed by native mammals, such as low water requirements and the ability of macropods to utilise low quality foods, suggest that drought is very much the norm in arid Australia (Freudenberger et al 1989). Despite their adaptations to the climate, native mammals, like introduced mammals, show marked population declines during periods of rainfall deficiency (Corbett and Newsome 1987;Short et al 1997;Dickman et al 1999b;Pople et al 2000). Several authors have suggested Figure 13.…”
Section: Environmental Change In the Northern Simpson Desertmentioning
confidence: 94%
See 1 more Smart Citation
“…The wide array of adaptive responses to periods of low rainfall displayed by native mammals, such as low water requirements and the ability of macropods to utilise low quality foods, suggest that drought is very much the norm in arid Australia (Freudenberger et al 1989). Despite their adaptations to the climate, native mammals, like introduced mammals, show marked population declines during periods of rainfall deficiency (Corbett and Newsome 1987;Short et al 1997;Dickman et al 1999b;Pople et al 2000). Several authors have suggested Figure 13.…”
Section: Environmental Change In the Northern Simpson Desertmentioning
confidence: 94%
“…In western New South Wales, these changes are thought to have depleted food resources for native mammals during periods of rainfall deficiency to critically low levels, contributing to the extinction of many species (Lunney 2001). In addition, the successful control of dingoes and provision of artificial waters appears to have allowed the maintenance of higher density populations of kangaroos, emus, feral goats, feral pigs and foxes than in non-pastoral and cattle grazing areas (Pople et al 2000;Newsome et al 2001). As a consequence, the availability of surface water and carrion during periods of rainfall deficiency may buffer populations of foxes and cats, thus elevating predation pressure on drought-stressed small and medium-sized vertebrates (Newsome et al 1989;Saunders et al 1995).…”
Section: Environmental Change In the Northern Simpson Desertmentioning
confidence: 96%
“…There is compelling evidence that dingoes help regulate the distribution and abundance of herbivores, leading to different grazing regimes and associated vegetation changes (Newsome et al, 1983;Robertshaw and Harden, 1986;Newsome, 1990;Pople et al, 2000). In addition, reviews by Glen and Dickman (2005) and Johnson et al, 2007 speculate that the dingo may also assert predatory and competitive dominance over the introduced red fox and feral cat, tempering their negative environmental effects (see also Newsome et al, 1997Newsome et al, , 2001Mitchell and Banks, 2005).…”
Section: The Dingo In Australiamentioning
confidence: 94%
“…Red kangaroos are protected on the 38,888-ha field station and foraged freely throughout the lower elevation sheep paddocks. The station is south of the dingo fence (Pople et al 2000), thus dingoes (Canis lupus dingo) currently do not represent an important risk of predation. Other potential predators (red foxes, Vulpes vulpes, and wedge-tailed eagles, Aquila audax) are locally common.…”
Section: Subjects and Study Sitementioning
confidence: 99%